Moral Particularism: An Introduction - Kirchin, Simon (Journal of moral philosophy, 2007)
Abstract Moral particularism is a contentious position at present and seems likely to be so for the foreseeable future. In this Introduction, I outline and detail its essential claim, which I take to be, roughly, that what can be a reason that helps to make one action right need not be a reason that always helps to make actions right. This claim challenges a central assumption on which most, if not all, normative ethical theories are supposedly based. We owe this way of characterizing moral particularism to Jonathan Dancy, around whose writings much of the present debate revolves.